SENSORY PROFILE OF 3 IN 1 INSTANT COFFEE USING EMOTIONAL-SENSORY MAPPING, FLASH PROFILE, AND CATA (CHECK-ALL-THAT-APPLY) METHODS - Dase Hunaefi; Wicensky Marusiva (Jurnal Teknologi dan Industri Pangan, 2021)
Three in one instant coffee is popular among university students. A variety brands of such instant coffee are available on the market. However, the literature on the sensory aspects of the instant coffee is rather limited slim. The project aimed to test three-in-one instant coffee sachets for their sensory characteristics. Two methods, CATA (Attributes and Emotional Mapping) and Flash Profile (extension of Free Choice Profiling) were employed to generate the attribute profiles and emotional dashboard. Sixty IPB University students were selected as panelists. Sensory attributes terminologies and their relation to emotion were generated using Focus Group Discussion among instant coffee heavy drinker. Profile of coffee D showed a creamy texture, while sweetness and milky was dominant when it came to coffee B and coffee C. The creaminess in coffee G was strongly related to feelings of happiness in a consumer. In addition, the sweet and milky taste and flavor in coffee B was seen as a relaxing and luxurious feeling. A Preference Mapping was constructed, and it showed that sweetness, milky, and creaminess improved the liking of the student consumers that make coffee C the most preferred brand among the panelists. In short, the use of flash profiles and check-all-it-dilute/CATA (attributes and emotional) equipped with preference mapping can provide emotional attributes and dashboards that will be important to understand products more than just consumer liking.